2019
DOI: 10.1016/j.jtemb.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the dietary intake of calcium, magnesium, iron, zinc and copper in institutionalised children and adolescents from Guatemala. Contribution of nutritional supplements

Abstract: In childhood and adolescence an adequate mineral intake is essential for normal growth and immune function, and to prevent chronic diseases in adulthood. The aim of this study was to analyse the dietary intake of Ca, Mg, Fe, Zn and Cu in children and adolescents from an orphanage-school in Guatemala and to assess the mineral contribution of nutritional supplements used by this population. Mineral content was analysed in nutritional supplements, bioaccesible fractions obtained after an in vitro gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…From this study, five beers have a concentration above the permissible limits of the food regulation NTE INEN 2262 [33] (0.2 mg L −1 ), so the consumption of these drinks is not accepted. Since iron is an essential element of the human diet, the intake between 10-20 mg day −1 [76,77] is recommended; however, it should not exceed 20 mg day −1 since it can cause damage to health, as stated by Ho Wang (2022) [78].…”
Section: Discussionmentioning
confidence: 99%
“…From this study, five beers have a concentration above the permissible limits of the food regulation NTE INEN 2262 [33] (0.2 mg L −1 ), so the consumption of these drinks is not accepted. Since iron is an essential element of the human diet, the intake between 10-20 mg day −1 [76,77] is recommended; however, it should not exceed 20 mg day −1 since it can cause damage to health, as stated by Ho Wang (2022) [78].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, methods of combating hidden hunger included optimized food system strategies, biofortification, food-to-food fortification, knowledge intervention, micronutrient replacement, and nutritional supplements [37][38][39][40][41][42]. However, although positive policies have been introduced and a decreasing trend has appeared, hidden hunger is still a major public health problem across the world [3,13,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed a positive correlation between dietary diversity and micronutrient adequacy, and dietary diversity indicators including dietary diversity scores (DDS) and food insecurity (FI) assessment tools including household food security survey (HFSS) have been used for screening hidden hunger [48][49][50]. However, the possible impact of bioaccessibility also needs to be considered in the assessment, which seems to be neglected in previous research [42]. The bioaccessibility of a compound is its ability to be absorbed from the gastrointestinal tract after it has been released from its matrix [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leaf contains trace elements that are essential to human health. For instance, magnesium, iron, selenium, and zinc play an important role in metabolism, and interest in these elements is increasing together with reports relating trace element status and oxidative diseases [45,46]. Despite all the benefit of these biochemical constituents, it also caused allowed of side effect especially in blood tissues.…”
Section: Discussionmentioning
confidence: 99%